Reducing STEM Attrition: Leveraging Digital Tools to Enhance Student Engagement and Success - Mohandsa, Dr. Ahmed; Stephen, Mike (Journal of Innovation in Education and Social Research, 2024)
STEM attrition remains a critical challenge in education, with many students leaving Science, Technology, Engineering, and Mathematics (STEM) fields due to disengagement, academic difficulties, or lack of support. As digital tools become increasingly prevalent in education, their potential to reduce attrition rates by fostering engagement, offering personalized learning experiences, and providing academic support is gaining recognition. This article explores how leveraging digital tools, such as adaptive learning platforms, virtual labs, and interactive simulations, can enhance student engagement, improve academic performance, and ultimately reduce STEM attrition. By examining case studies and research, we highlight the transformative power of these tools in creating a more inclusive and effective STEM learning environment.